Evolutionary Rent-Seeking - Burkhard Hehenkamp; Wolfgang Leininger; Alex Possajennikov (Center for Economic Studies and ifo Institute (CESifo), 2001)
Tullock's analysis of rent-seeking is reconsidered from an evolutionary point of view. We show that evolutionarily stable behavior in a rent-seeking contest differs from efficient rent-seeking behavior in a Nash equilibrium. We explore that implications of evolutionary stability for rent-seeking behavior and relate them to the well examined Nash equilibrium behavior. A most interesting result is an overdissipation law, which holds in evolutionary equilibrium.
Keywords: 330